PARALLEL PROCESSES IN EDUCATION SYSTEMS IN SPAIN AND RUSSIA DURING AND AFTER CORONAVIRUS - Tatiana Victorovna, Sedova (Revista Inclusiones, 2020)
The aim of the article is to analyze parallel processes in educational systems in the Russian Federation and the Kingdom of Spain. These are processes of increasing investment in education in both countries and of replacing, in a regulatory or spontaneous manner, pre-school, school and higher education teachers, over 65 years of age, with younger colleagues. For researching was used the method of monitoring materials of INTERNET, press and mass media. Spain's comparative analysis of difficulties in rejuvenating the pedagogical composition in preschool and schools by 30% in 2012, which, in fact, almost overwhelmed the entire Spanish education system due to the impossibility of filling vacancies by people who had not passed the state exams, gives the possibility to predict that Russia will be able to optimize school staffs. The first way will be to replace them with students of higher education and the second will be to cover the staff by acting teachers and pruralists. The combination of these approaches will be applied according to the needs of each federative entity. The last route will be especially effective for schools profiled within universities.